Analysis of the Talking Stick Model and the Expository Method on Math Learning - Muludin Rofik; Rikrik Nurdiansyah; Yayu Nurhayati Rahayu (Gunung Djati Conference Series, 2022)
The goal of this paper is to look at how the talking stick model and the expository method affect arithmetic learning. The descriptive research and literature review methods were used in this study (library research). Content analysis was employed to analyze the data in this study. The data for this study was gathered from a variety of sources in the library, including reference books, similar earlier research results, articles, notes, journals, e-books, and websites. The findings of this study provide an examination of the impact of the talking stick type of learning model and the explanatory technique on mathematics learning